2011
DOI: 10.1021/ct200462q
|View full text |Cite
|
Sign up to set email alerts
|

IDSite: An Accurate Approach to Predict P450-Mediated Drug Metabolism

Abstract: Accurate prediction of drug metabolism is crucial for drug design. Since a large majority of drugs metabolism involves P450 enzymes, we herein describe a computational approach, IDSite, to predict P450-mediated drug metabolism. To model induced-fit effects, IDSite samples the conformational space with flexible docking in Glide followed by two refinement stages using the Protein Local Optimization Program (PLOP). Sites of metabolism (SOMs) are predicted according to a physical-based score that evaluates the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 42 publications
0
52
0
Order By: Relevance
“…If the distance was less than 3·5 Å, the site was considered to be exposed to the haem centre, and a quantum mechanics calculation was performed to obtain the hydrogen abstraction energy. To further consider the effect of protein flexibility during the ligand-binding process, Li et al reported a CYP-mediated SOM prediction model based on induced-fit docking, where the conformations were refined with the Protein Local Optimization Program (Li et al 2011b). The testing of the IDSite on CYP2D6 showed that the IDSite could recover 83% of the experimentally observed SOMs for 56 compounds with a low false positive rate.…”
Section: Som Predictionmentioning
confidence: 99%
“…If the distance was less than 3·5 Å, the site was considered to be exposed to the haem centre, and a quantum mechanics calculation was performed to obtain the hydrogen abstraction energy. To further consider the effect of protein flexibility during the ligand-binding process, Li et al reported a CYP-mediated SOM prediction model based on induced-fit docking, where the conformations were refined with the Protein Local Optimization Program (Li et al 2011b). The testing of the IDSite on CYP2D6 showed that the IDSite could recover 83% of the experimentally observed SOMs for 56 compounds with a low false positive rate.…”
Section: Som Predictionmentioning
confidence: 99%
“…Should a prediction only consider the atoms that are closest, or could any additional atoms also be considered? More elaborate geometric criteria may circumvent this problem [10].…”
Section: å Rulementioning
confidence: 99%
“…Interestingly, a very simple approach such as SMARTCyp (see Chapter 11), which is based solely on the intrinsic reactivity of potential SoMs, performs very well to predict the SoM of substrates of CYP1A2 and 3A4, but an orientational penalty needs to be included for isoforms 2C9 and 2D6 [11][12][13]. Ideally, a structure-based approach should be combined with an estimate of the intrinsic reactivity, which is the key idea behind approaches such as MetaSite [7], MLite [14], or IDSite [10]. The first of these approaches combines a quantum mechanical calculation to describe the reactivity with a fingerprint match between the substrate and the active site [7] (see Chapter 9).…”
Section: å Rulementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these solely ligand-based strategies, other computationally more demanding approaches to prediction SOMs include the protein environment via docking [64][65][66]. On the other hand also data-driven approaches were found to yield accurate results at a comparably low computational cost.…”
Section: Som Predictionmentioning
confidence: 99%